Defect Point Location Method of Civil Bridge Based on Internet of Things Wireless Communication - Xiaofeng Yan; Zedong Liu; Zijing Zhuang; Yong Miao (Journal of Electrical and Computer Engineering)
With the growth of the country’s comprehensive strength, China’s road and bridge traffic is also growing rapidly. Therefore, the maintenance of highway bridge pavement has become extremely important. The main manifestation of highway bridge deck diseases is bridge deck cracks. If the bridge deck cracks are found in the early stage of damage and solved in time, it will undoubtedly greatly reduce the maintenance cost and care and ensure that the road can be driven safely. At present, the detection of highway bridge defects is mainly based on human vision, but this kind of artificial visual inspection is difficult to complete efficiently. The purpose of the article was to study image recognition techniques and measure the surface damage to bridge superstructures. It has also developed an intelligent software system that can measure and identify cracks under bridges. Aiming at the compatibility problem of wireless communication front end caused by the difference in wireless communication protocols, this study designs a high-applicability front-end control interface for wireless communication. After testing, data can be sent and received when the I/O mode rate drops to 10 Kbps. This method is severely limited and is not suitable for IoT applications with low power consumption and low frequency. It uses the SPI interface for communication and can send and receive normally at different rates, with an upper limit of 8 Mbps. This method consumes a little more pins, but the clock signal is stable, and the transmission performance can meet the needs of most applications.